Pengaruh Workplace Bullying, Workplace Gossip dan Workplace Incivility Terhadap Turnover Intention pada Pekerja Gen Z di Kota Surakarta - Putri Okti Anjarwati; Nike Larasati (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This quantitative survey research was conducted in Surakarta, Central Java, with a focus on Generation Z workers. The objective of this study was to examine the influence of workplace bullying, workplace gossip, and workplace incivility on turnover intention. This study employed non-probability sampling techniques with a purposive sampling approach, utilising primary data collected from 150 respondents through a validated and reliability-tested questionnaire. The analysis of the data was conducted through the utilisation of classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R2). The findings indicated that workplace bullying and incivility did not exert a substantial influence on the intention to turnover. In contrast, workplace gossip was found to have a significant effect. Furthermore, the coefficient of determination (R²) of 18.2% indicates that the three independent variables only contribute a small portion (18.2%) of the variation in intention to leave, while the remaining 81.8% is influenced by factors outside the model studied.